2017
DOI: 10.1039/c7ra08841h
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline carbon coated alumina with enhanced phase stability at high temperatures

Abstract: The carbon coating hinders the sintering of the δ-Al2O3 phase. The stabilization of the nanosized oxide particles in the Al2O3@C system is considered as the decisive factor preventing their transformation to the α-Al2O3 phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…As shown in Table , the BET surface area of Al 2 O 3 - x decreases with increase of calcination temperature, which is in consistent with previous reports. The XRD patterns of Al 2 O 3 - x samples are shown in Figure . All the peaks attributable to γ-Al 2 O 3 are observed in the XRD pattern of Al 2 O 3 -800.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Table , the BET surface area of Al 2 O 3 - x decreases with increase of calcination temperature, which is in consistent with previous reports. The XRD patterns of Al 2 O 3 - x samples are shown in Figure . All the peaks attributable to γ-Al 2 O 3 are observed in the XRD pattern of Al 2 O 3 -800.…”
Section: Resultssupporting
confidence: 90%
“…With increasing calcination temperature, the intensities of the α-Al 2 O 3 peaks grow while those of θ-Al 2 O 3 significantly decrease. Ultimately only the diffraction peaks of α-Al 2 O 3 are identified on Al 2 O 3 -1300, indicating that alumina has been transformed to α-Al 2 O 3 at 1300 °C, which is in good agreement with reported results. A similar conclusion on the phase transformation of alumina can also be drawn from Rietveld analysis (Figures S1–S4 and Table S1 of the Supporting Information, SI).…”
Section: Resultssupporting
confidence: 86%
“…For instance, Volodin et al showed that carbon-coated δ-Al 2 O 3 nanocrystals are highly stable in high-temperature regions. [45] This suggests that the MOF-derived B-TiO 2 embedded carbon matrix is naturally produced during the pyrolysis process, and the resultant Figure 3c shows the cyclic voltammetry (C-V) curves of the DP-TiO 2 @C samples measured in the potential range of 0.01-3.0 V. All samples show clear oxidation peaks at 1.55-1.66 V (for B-TiO 2 ) and 2.1 V (for A-TiO 2 ). [25,46] As shown in Figure 3c and Figure S6 (Supporting Information), the current density of the redox peaks of B-TiO 2 appears to be more dominant in DP-TiO 2 @C-500, and the current density of the redox peaks of A-TiO 2 tends to increase with increase in the temperature of the second step of pyrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…In literature the only exception is the carbon coated alumina that hinders the sintering of the δ-Al 2 O 3 22,23 .…”
Section: Nitrogen Isotherms and Specific Surface Areamentioning
confidence: 99%